Semiconductor quantum light sources : Fundamentals, technologies and devices - Michler, Peter; Portalupi, Simone Luca
The work provides fundamental expertise of quantum optics and photonic quantum technology with particular attention to the generation of non-classical light with semiconductor nanostructures. The book is written by experimentalists for experimentalists at various career stages: physics and engineering students, researchers in quantum optics, industry experts in quantum technology. A didactical structure is followed, having in each chapter overview and summary of the discussed topics, allowing for a quick consultation.
Includes bibliography and index
Keywords: Photonic engineering; Single-photon sources; Quantum optics; Semiconductor nanostructures